Technology adoption of digital banking and women consumers: An empirical investigation - Kaur, Bimaldeep; Batra, Narinder Kaur (International Journal of Experimental Research and Review, 2023)
Digital banking services have gained much attention in recent years due to their enormous advantages, like convenience, flexibility, and time-savings compared to traditional banking services. However, the low awareness, perceived risk, and security concerns with online banking services led Indian women to deposit their savings in banks, mostly in accounts operated by the husband or a male family member. This study examines women consumers' awareness and intentions to use digital banking during post-demonetization. The study has analyzed the technology adoption model and established a relationship between perceived usefulness, ease of use, trust, risk and behaviour (independent variables) and intentions to use (dependent variable). We have carried out a primary survey and collected 180 responses from the national capital regions of India. The findings show a positive significant influence of perceived usefulness, ease of use, and behaviour over the intentions to use digital banking. According to the outcome, women consumers are ready to adopt digital banking. The results of this study may be utilized to improve financial services, particularly digital banking, and as part of a marketing campaign to promote its usage. It has been difficult to visit the bank physically during epidemics; thus, using digital banking is strongly advised.